(untitled) (Journal of Intellectual Property Rights (JIPR), 2023)
Traditional knowledge (TK) is going multidimensional. On one side it is penetrating Intellectual Property Rights (IPR) marking its association, besides Patents, with Trade Marks, Copyrights, Geographical Indication. On the other hand, the debate as to the protection of TK at the international level is gaining whilst becoming complex. The said debate is, still, not mature enough to have a legal protection covering benefit sharing. The paper discusses the multidimensional nature of TK. It is desired that this would throw light on different aspects of TK whilst analyzing that TK is really a complex concept when it comes to securing an international protection regime. The paper may allow ways to secure protection after witnessing the multidimensional nature of TK.